A musical view: the secret mechanics of a landscape - Luca Mantovani (Festival dell'Architettura Magazine, 2021)
This article is a sort of story in images about landscape photography. The author, an architect by training with significant experiences in the field of architectural photography, invites us to see the landscape with a "musical view" through the photographs of different places, mostly in the Po Valley (from Sabbioneta to Mantua, Pomponesco, Bagnolo San Vito, etc.). A short but dense text forms both the incipit and basic explanation of the article.